The method of discontinuities analysis in microstrip-slotline structures. Part 2: Analysis of complex discontinuities in the three-layered planar structures - Рассохина, Ю.В.; Крыжановский, В.Г. (Radiotekhnika, 2017)
Algorithms for analysis of inhomogeneities in the form of a jump of width in a microstrip transmission line of a finite length (inductive and capacitive segments) with the addition of rectangular slot resonators in ground plane were constructed. Fast convergence of the algorithms was achieved through description of the functions of the current density in an inhomogeneous microstrip transmission line using vector potentials for them. Addition of the slotted resonators on the ground plane to the diagram on the stepped discontinuity results in the appearance of additional frequencies of the resonant reflection and transmission, in comparison with the conventional stepwise inhomogeneities This makes it possible to improve performance and expand functionality of the designed filters and matching circuits.